INFLUENCE OF PRODUCT QUALITY AND DESIGN ON THE PURCHASE DECISION OF HONDA CRV MOTOR VEHICLES AT PT. SINAR SENTOSA (CASE STUDY IN JAMBI CITY) - Mappedeceng, Riko (Dinasti Publisher, 2021)
This study aims to determine the effect of product quality and design on purchasing decisions on Honda CRV motor vehicles in Jambi City. The research methodology used is a quantitative method. The data used are secondary data and primary data. the population in this study were consumers of PT. SINAR SENTOSA who are consumers of CRV motorcycle users with a sample of 81 people. The analysis is regression test, T test and F test. The results of this study indicate that the application of product quality to consumers who have purchased a Honda CRV motor vehicle. product quality has a positive and significant effect on purchasing decisions for Honda CRV motor vehicles. expected PT. SINAR SENTOSA JAMBI will improve quality and design, in order to attract consumers to buy a Honda CRV motor vehicle.